2011
DOI: 10.1007/s10409-011-0484-2
|View full text |Cite
|
Sign up to set email alerts
|

Incubation time fracture criterion for FEM simulations

Abstract: The paper is discussing problems connected with embedment of the incubation time criterion for brittle fracture into finite element computational schemes. Incubation time fracture criterion is reviewed; practical questions of its numerical implementation are extensively discussed. Several examples of how the incubation time fracture criterion can be used as fracture condition in finite element computations are given. The examples include simulations of dynamic crack propagation and arrest, impact crater format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Such solutions, as a rule, are not applicable to the analysis of real problems, but can be used to validate and assess the accuracy of the developed numerical models. In most cases, the problem posed can be solved only numerically using approximate methods for solving the resulting systems of differential equations (see, for example, [55]).…”
Section: Design Modelsmentioning
confidence: 99%
“…Such solutions, as a rule, are not applicable to the analysis of real problems, but can be used to validate and assess the accuracy of the developed numerical models. In most cases, the problem posed can be solved only numerically using approximate methods for solving the resulting systems of differential equations (see, for example, [55]).…”
Section: Design Modelsmentioning
confidence: 99%
“…It was shown that using the incubation time criterion incorporated into finite element code a correct prediction of dynamic fracture initiation [2,5], dynamic crack propagation [22] and fracture of initially fractured media [23] is possible.…”
Section: Incubation Time Fracture Criterionmentioning
confidence: 99%
“…There are relatively few treatments of transient modes in moving load problems, including early works (Payton, 1967;Gakenheimer and Miklowitz, 1969) and also more recent contributions (de Hoop, 2002;Kaplunov et al, 2010b). It is known that an analysis of transient dynamics is generally non-trivial, often requiring a numerical approach; refer to studies by Bratov (2011) and Smirnov et al (2012). We also mention active studies of moving loads on elastic structures, for example refer to a textbook (Fryba, 1999) and references therein, as well as recent works in studies by Dimitrovová (2017), Wang et al (2020) and Lu et al (2020).…”
Section: Introductionmentioning
confidence: 99%